A Framing Analysis of Reporting on Student Actions to Forcefullu Expel Rohingya in Tirto.id and BBC Indonesia - Putri, Safira Ramadhani; Hariyanto, Didik (Universitas Muhammadiyah Sidoarjo, 2024)
This research analyzes the differences in the framing of the student action that forcibly expelled Rohingya refugees in Aceh in two media, namely Tirto.id and BBC Indonesia. Using a descriptive qualitative approach with Robert Entman's framing analysis method, this research seeks to reveal how the two media framed the event through reporting. The research results reveal significant differences in the framing of events by the two media, which can be attributed to the background, philosophy and agenda of each media. Tirto.id, with its approach to precision journalism and covering both sides, frames this action as the result of socio-economic complexity and local dynamics, while BBC Indonesia focuses more on the humanitarian dimensions and moral implications of the event. These findings highlight the importance of understanding media background in framing analysis, as well as how agenda setting can influence the way an event is reported to the public.